Vestibular Evoked Myogenic Potentials Are Abnormal in Idiopathic REM Sleep Behavior Disorder - de Natale, Edoardo Rosario; Ginatempo, Francesca; Laccu, Ilaria; Figorilli, Michela; Manca, Andrea; Mercante, Beniamina; Puligheddu, Monica; Deriu, Franca (Frontiers in Neurology, 2018)
OBJECTIVES: To investigate brainstem function in idiopathic REM sleep Behaviour Disorder (iRBD), a condition occurring as a result of a derangement of connections within brainstem structures, with a battery of Vestibular Evoked Myogenic Potentials (VEMPs), neurophysiological tools suited for the functional investigation of the brainstem. Neurophysiological data were correlated with clinical characteristics of patients. METHODS: 20 patients with iRBD and 22 healthy controls underwent cervical (cVEMP), masseter (mVEMP) and ocular (oVEMP) VEMP recording. Patients were assessed clinically according to presence of motor as well as non-motor symptoms such as constipation, depression and hyposmia. Also, they were screened for postural instability through the Berg Balance Scale (BBS). VEMPs were categorized as for increasing degrees of abnormalities, namely latency delay, amplitude reduction and absence; a VEMP score was built accordingly. RESULTS: compared with controls, iRBD had higher rates of abnormalities both in the VEMP battery (iRBD 75%, Controls 23%; p<0.01) as well as in each single VEMP (cVEMP: 45% versus 5%; mVEMP: 65% versus 13.6%; oVEMP: 50% versus 5%; p<0.01), which exhibited significantly lower amplitudes (cVEMP and oVEMP: p<0.0001; mVEMP: p=0.001) in iRBD. Within altered reflexes, absence was predominant in oVEMP (81%), amplitude reduction in mVEMP (50%) and cVEMP (70%). Severity of VEMP alterations was significantly higher in iRBD compared with controls (p<0.05 for all VEMPs), as indicated by the larger VEMP scores in the former. The oVEMP score correlated inversely with poor performances on the BBS. CONCLUSION: VEMPs unveil consistent and extensive brainstem abnormalities in iRBD patients. Further studies are warranted for testing the potential of VEMPs in the monitoring of the evolution of iRBD over time.